A framework for planning academic library spaces - Choy, Fatt Cheong (2016)
Purpose: The focus on designing spaces for users in the last decade or so signifies the gradual change in the mission of libraries from provision of resources to that of a pro-active partner in learning. Planning for user space in support of learning is far more complex as it needs to take into account the variety of users’ needs and behaviour. Before specifying the actual layout and design of users’ spaces it is important to consider all the major factors that affect the use of the intended library space. The purpose of this paper is to provide a guide to library planning base on the experience of the authors at Nanyang Technological University (NTU) Libraries.